2020
DOI: 10.1002/adfm.202004273
|View full text |Cite
|
Sign up to set email alerts
|

A Multilayered Electron Extracting System for Efficient Perovskite Solar Cells

Abstract: Power conversion efficiencies of perovskite solar cells (PSCs) have rapidly increased from 3.8% to a certified 25.2% within only a decade. Eliminating possible recombination losses at the interfaces is essential to further improve both efficiency and stability of this class of emerging photovoltaic technology. Herein, a simple approach for improving the electron extraction of the PC 60 BM electron transport layer (ETL) is presented by sequentially depositing Al:ZnO (AZO) and triphenyl-phosphine oxide (TPPO) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…We further investigated charge-transport properties of PSCs with and without SrCl 2 by using TPV measurements. The TPV curve revealed that incorporation of SrCl 2 increased the charge-carrier lifetime (Figure 6C), indicating a decrease in the undesired charge-carrier recombination (Seitkhan et al, 2020). As shown in Supplementary Figure S4, the ideality factor (m) was measured to evaluate the recombination process in PSCs.…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated charge-transport properties of PSCs with and without SrCl 2 by using TPV measurements. The TPV curve revealed that incorporation of SrCl 2 increased the charge-carrier lifetime (Figure 6C), indicating a decrease in the undesired charge-carrier recombination (Seitkhan et al, 2020). As shown in Supplementary Figure S4, the ideality factor (m) was measured to evaluate the recombination process in PSCs.…”
Section: Resultsmentioning
confidence: 99%
“…For these devices, a poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) hole-transport layer and Nb-TiO 2 +BCP electrontransporting bilayer were used, as demonstrated elsewhere. [27,28] This blend of PTB7-Th:IEICO-4F was selected over newer, higher efficiency blends such as PM6:Y6 so as not to limit the current of the tandem device resulting from PM6:Y6's blueshifted absorption edge. A PM6:Y6-containing device was measured beneath a semitransparent a-Si:H device to simulate its use in a tandem structure (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…16, Top ETL is an irreplaceable layer for high performance inverted PSC and inevitably resolve the device stability. 3,6,29,34,42,45,63,65,71,81, Therefore, high stability of top ETL will enhance the stability of PSCs and promote the device commercialization.…”
Section: Principles Of Top Etlmentioning
confidence: 99%
“…[3][4][5] As an important functional layer in high performance inverted PSC, electron transport layer on top of perovskite film (namely top ETL) play an irreplaceable role. Known to be a star ETL, fullerene and it derivative such as [6,6]phenyl-C61-butyric acid methyl ester (PCBM) has been widely used in inverted PSCs, exhibiting negligible hysteresis. [6][7][8][9][10] However, difference between the Fermi level of PCBM and the work function of Ag electrode often results in Schottky barrier at their interface, 11 leading to charge carrier recombination and high series resistance (R S ) and thus low PSC performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation